The Development of Health Station in Buriram Province - ชุดไธสง นิตยา (Journal of Health Science of Thailand, 2026)
The COVID-19 pandemic has significantly affected the non-communicable disease (NCD) service system due to reduced hospital services under social distancing policies. Meanwhile, the number of NCD patients continued to rise, requiring the health service system to adapt appropriately to the prevailing situation. This action research aimed to develop a service model for health stations in Buriram Province. The study was conducted in three phases: (1) to analyze the situation and assess service needs; (2) to design and develop Health Stations in communities using the Ottawa Charter for Health Promotion as a conceptual framework; and (3) to evaluate the outcomes of the health station implementation. The purposive samples consisted of multidisciplinary health teams, community partners 107 people and service users 35,452 people of the health stations between May 2019, and May 2022. The research instruments included interview forms, observation records, and problem-solving plans based on the AIC (Appreciation–Influence–Control) participatory process, along with laboratory data. The data were analyzed using descriptive statistics and qualitative content analysis. Phase 1: the findings indicated that health promotion services among the population still relied heavily on public health personnel. People lacked tools and skills for self-care and for reducing their risk of developing diseases. Phase 2: planning and development activities revealed five key results: (1) developing public health policy for health promotion through the participation of all sectors in recognizing common problems, setting shared goals,and defining standards, roles, funding sources, service delivery systems, and management of health stations; (2) creating supportive environments for health, with every community establishing a health station according to the designated standards and guidelines; (3) strengthening community health actions through continuous health promotion activities to solve problems collaboratively; (4) developing individual skills for self-care and building capacity for health coaches; and (5) reforming the health service system into a people-centered model, linking services with health stations and integrating data among service units. Phase 3: the evaluation of Health Station implementation found that Buriram Province had established 2,596 health stations, with 75.07% of funding supported by local administrative organizations. Regarding health outcomes, access to public health services in 2022 showed remarkable improvement: 90% of the population received health screening 90.87% of suspected cases were followed up for diagnosis and 61.28% of hypertensive patients achieved good disease control, which represented an increase compared with the previous year. The implementation of the health station model effectively reduced congestion and waiting times in hospitals. Overall, the development of health stations in Buriram Province laid a solid foundation for primary health promotion systems, emphasizing self-reliance among the population and sustainable health development in the community.